THE IMPLEMENTATION OF TPS IN TEACHING SPEAKING AT AGROTECHNOLOGY DEPARTMENT UNIVERSITAS GUNUNG LEUSER ACEH - ZAINI HASAN (JURNAL ILMIAH MAKSITEK, 2018)
The objective of this research is to improve students’ speaking ability using Think-Pair-Share of cooperative learning for the students of Agrotechnology department Universitas Gunung Leuser. This particular research was categorized as action research. The actions were implemented in two cycles based on the class schedule. This research involved 33 students of Agrotechnology departmentin the academic year of 2018/ 2019 and the English lecturer as the research collaborator. The data of the study were in the forms of qualitative and quantitative data. The qualitative data were obtained by observing the teaching and learning process and interviewing the students of Agrotechnology department and the English lecturer. Meanwhile, the quantitative data were acquired conducting through the pre-test, the progress test, and the post test. The validity of the data was obtained by applying democratic, dialogic, catalytic, and outcome validity. The procedure of the research consisted of reconnaissance, planning, acting, reflecting, and revising plan. The results of this research show that the use of the Think-Pair-Share technique was able to improve the students’ speaking ability. Based on the qualitative data, applying Think-Pair-Share technique gave the students more chances to speak in English. The students became more confident to speak up English. They actively participated during the teaching and learning process. The use of classroom English helped the students to be more familiar with English. The vocabulary practice and pronunciation drill also helped them to enrich their vocabulary knowledge and build their accuracy. These findings were also supported by the result of the students’ speaking scores. The mean improved from 58.55 in Cycle I to 77.60 in Cycle II. It indicated that they made a considerable improvement in some aspect of speaking skills such as pronunciation, intonation and stress, comprehension, grammar, and vocabulary